Phytochemical and Pharmacological Investigations of Genus Cassia: A Review - Agarkar, S.V.; Jadge, D.R. (Asian Journal of Chemistry, 2010)
Genus Cassia, a tropical genus, belongs to Leguminosae family and Caesalpiniaceae subfamily. It is well known to physicians from very old days. It has more than 600 species as herbs, shrubs and trees. About 26 species of genus Cassia have been reported to contain anthracene derivatives. The more important species among them are Cassia alata, Cassia angustifolia vahl, Cassia autifolia, Cassia cinnamon, Cassia fistula, Cassia nodosa, Cassia obtusifolia, Cassia sophera, Cassia tora and Cassia zeylanicum. Diuretic, antidiabetic, antibiotic, antifungal, antipyretic, anthlemintic, antibacterial, antirheumatic, anti-eczema, antiherpetic, antiasthrnatic, anti-leprosy, anti-typhoid and anti-bronchitis activities have been reported from some of these species.